Plagiarism awareness among library and information studies students at the University of Ibadan: implications for quality assurance (2016)
With the explosion of information on the Internet, there is need for adequate enlightenment on the use of information for academic purposes without resorting to plagiarism. The study examined the level of awareness of plagiarism among the University of Ibadan library and information science students. Survey research design was adopted for the study. Eighty-four students, constituting about 60% of the undergraduate and postgraduate students at 400, 700 and 800 levels respectively were surveyed in the study. Questionnaire was used as instrument for data collection. The findings indicated that students were aware of various acts of plagiarism, as well as the implications. They were also taught how to avoid plagiarism in their research work. The level of knowledge of students on plagiarism was high as many had taken courses that mentioned the academic crime of plagiarism. Some of the students indicated that they had been involved in plagiarism before and were ready to desist from such act. Some fundamental problems that need to be solved to reduce incidents of plagiarism were identified to include: inadequate knowledge of appropriate use of Internet resources and lack of current information resources in the university library. The paper highlights some expectations from lecturers in LIS curricula and recommends that there should be more enlightenment programmes for students through lectures and curriculum redesign. The lecturers are advised to use plagiarism detector software to check students' projects against plagiarism before submission. The university libraries should be stocked with current information resources to reduce incidents of plagiarism in Nigerian LIS schools.